The Role of Sharia Management in the Development of Micro, Small, and Medium Enterprises (MSMEs) - Mahadewi, Erlina Puspitaloka; Al-Amin, Al-Amin; El Hasan, Sawqi Saad (International Journal of Sharia Business Management, 2024)
This study aims to explore the role of sharia management in the development of Micro, Small, and Medium Enterprises (MSMEs) and how the application of sharia principles can improve the performance and sustainability of MSMEs. The research method used is a qualitative approach with data collection techniques through literature studies, in-depth interviews with MSME actors, and document analysis from Islamic financial management institutions. The results of the study indicate that the application of sharia management in MSMEs, including principles such as transparency, fairness, and the prohibition of usury, contributes significantly to the development of these businesses. Sharia principles not only help in managing risks more effectively but also increase customer trust and loyalty. The conclusion of the study confirms that sharia management plays an important role in facilitating the growth and sustainability of MSMEs by introducing ethical business practices that are in accordance with Islamic values, as well as increasing MSME access to more integrated financing and support.